Strategi Badan Penanggulangan Bencana Daerah Kabupaten Katingan Dalam Penanganan Bencana Kebakaran Hutan Dan Lahan Gambut Di Kecamatan Katingan Hilir Kabupaten Katingan: The Strategy Of Regional Disaster Management Agencies In Katingan District In The Handling Of Forest Fire And Peat Land In Katingan Downstream Of Katingan Regency - Muqsith, Leda Al; Rinto, Rinto (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
Forest fires and peatlands affect the destruction of the ecosystem and the manhood of the flora and fauna that grows and lives in the forest. The smoke caused also becomes air pollution that can cause diseases of the respiratory tract such as upper respiratory tract infections (ISPA), asthma, chronic obstructive pulmonary disease. Also, smoke can interfere with visibility, especially for aviation transport. The BPBD of Katingan Regency became the hope of the government in the handling of forest and land fires, so that forest fires and peatlands can be reduced annually. This research aims to know the strategy of BPBD in Katingan Regency in the handling of fire and peat land in Katingan district downstream of Katingan Regency. The research approach used is qualitative. Results Adapaun shows that the BPBD strategy of Katingan Regency in the implementation of forest fire and peatland in the region of Katingan Hilir, by involving the human resources that exist in the BPBD regency of Katingan.